3 GPa dual-phase stainless steel from synergistic heterogeneous structure and nano-precipitate - Qiang Li; Lichu Zhou; Hong Gao; Yijie Pan; Jinfeng Ma; Xiaodan Zhang; Jianqing Jiang; Feng Fang (Materials Research Letters)
Grain refinement is the most common strategy to improve the mechanical performance of metals such as strength, wear resistance and fatigue. For the 2101 duplex stainless steel (DSS), a heterogeneous microstructure composed of sub-25 nm fiber grains and submicron elongated grains was successfully prepared by heavily drawing taking advantage of the heterogeneous microstructural design. The DSS possesses ultra-high strength of 3 GPa which is 15% higher than the reported that of DSS or a leading strength-ductility combination of 1.43 GPa and 17%. This study provides a strategy for heterogeneous microstructural design to achieve excellent mechanical performance, specifically high strength.